Uncompahgre: Threads West # 3 : where water turns rock red - Rosenthal, Reid Lance (Cheyenne, Wyoming : Rockin' SR Publishing, 2014)
1850s. European women traveling across American must decide if they will abandoned love and return East or settle in the remote Uncompahgre Valley. Meanwhile an Oglala Sioux family struggles with the changes coming to their lands and a Mexican vaquero is driven north by the Texas Revolt.
"Third novel of the Maps of fate era novels (1854 to 1875) of the Threads West, American saga series."
new book 2023 summer.
Keywords: Frontier and pioneer life -- West (U S ) -- Fiction; Frontier and pioneer life -- Colorado -- Fiction; West (U.S.) -- History -- 1848-1860 -- Fiction; West (U.S.) -- History -- 1860-1890 -- Fiction; United States -- History -- 1849-1877 -- Fiction; Uncompahgre Valley (Colo.) -- Fiction; Colorado -- History -- 1876-1950 -- Fiction; Historical fiction; Romance fiction